Enhancement of Peroxidase Activity in Artificial Mimochrome VI Catalysts through Rational Design. (25th July 2018) - Caserta, Giorgio; Chino, Marco; Firpo, Vincenzo; Zambrano, Gerardo; Leone, Linda; D'Alonzo, Daniele; Nastri, Flavia; Maglio, Ornella; Pavone, Vincenzo; Lombardi, Angela
Abstract: Rational design provides an attractive strategy to tune and control the reactivity of bioinspired catalysts. Although there has been considerable progress in the design of heme oxidase mimetics with active‐site environments of ever‐growing complexity and catalytic efficiency, their stability during turnover is still an open challenge. Herein, we show that the simple incorporation of two 2‐aminoisobutyric acids into an artificial peptide‐based peroxidase results in a new catalyst (Fe III ‐MC6*a) with higher resistance against oxidative damage and higher catalytic efficiency. The turnover number of this catalyst is twice as high as that of its predecessor. These results point out the protective role exerted by the peptide matrix and pave the way to the synthesis of robust bioinspired catalysts. Abstract : By design : The simple incorporation of two helix‐inducing 2‐aminoisobutyric acid residues into an artificial peptide‐based peroxidase results in a new catalyst (Fe III ‐MC6*a) with higher resistance against oxidative damage and higher catalytic efficiency. The turnover number of this catalyst is twice as high as that of its predecessor. These results constitute an important step toward understanding how to engineer active and robust biocatalysts.